e-Governance: A Critical Review of e-Government Systems Features and Frameworks for Success - Palma, John Paul B.; Avila, Lindberg S.; Mag-iba, Maria Angelika J.; Buman-eg, Lorenza D.; Nacpil Jr., Edwin E.; Dayrit, Dave Joshua A.; Rodelas, Nelson C. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – To determine the key features, key performance indicators and framework for successfully implementing an e-governance system. Method – Exploratory research was made to understand better the opportunities and challenges in implementing an e-governance system. Six highly urbanized cities (HUC) were compared: Manila, Taguig, Pasay, Makati, Quezon, and Davao. To categorize, the three blocks of eGovernment services were utilized in grouping the process and features in the system: Government to Citizens (G2C), Government to Business (G2B), and Government to Government (G2G). These services were grouped according to each e-government block to determine commonalities and unique features. Results – In this study, the researchers identified four communication channels used by each city such as web portal, social media, mobile application, and web application. In addition, the common e-services for each block are: In the G2C category, the researchers have the real property tax, local civil registry, and community announcements e-services. In G2B, the researchers have occupational/health permits, business permit licensing, and business tax as the commonly offered e-services. Conclusion – This study identifies the types of e-government services and shows how the main components of the application can be categorized. In implementing an e-government system, it is highly recommended to start with the common G2C and G2B services. It is also essential to use multiple channels such as web portals, social media, mobile apps, and web apps to reach the different personas of the communities and to communicate government activities faster. Recommendations – To further this study, the researchers recommend empirical research using persona-based journey maps to establish the link of the KPIs mentioned in this study. Practical Implications – This research can be used by cities and municipalities still in the early adoption phase of e-governance systems. The standard e-government services can serve as a baseline for developing mobile and web applications to serve citizens and businesses better.